Elements Influencing Going Concern Audit Opinion on Manufacturing Corporations in Indonesia - Melati, Dewi; Sihono, Agus (Majalah Ilmiah Bijak, 2024)
This A going concern audit opinion is an audit opinion issued by an auditor to ensure whether the corporation can preserve its vicapability. Providing a going concern opinion is something that is not expected by the corporation because it can damage public trust and can even indicate bankruptcy. Meanwhile, for users of financial statements, going concern audit opinions are used as an initial warning to avoid errors in decision making. This watchfulness aims to re-verify empirically the clout of Profitability, liquidity, leverage and financial distress on going concern audit opinion. Purposive sampling method for sampling secondary data from the annual statements of 37 manufacturing corporations in the basic materials field listed on the Indonesia Stock Exchange for the watchfulness term 2020 - 2022. The data was analyzed executing binary logistic regression which was carried out in statistical analysis software. The outputs of this watchfulness denote that Profitability, liquidity, leverage and financial distress simultaneously clout going concern audit opinion. Then, leverage and financial distress have a positive clout on going concern audit opinion, while Profitability and liquidity have no clout on going concern audit opinion